Mengintegrasikan Budaya Lokal dalam Kota Cerdas: Kolaborasi Tata Kelola Berbasis ‘Sombere’ di Kota Makassar, Indonesia - Irfan Setiawan; Asep Hendra; Melianus Mesakh Taebenu; Ayu Widowati Johannes; Fathir Fajar Sidiq (Jurnal Bina Praja, 2024)
This research aims to examine the integration of local culture in a smart city. The novelty of this research introduces the concept of a Culturally Integrated Smart City, which emphasizes the importance of integrating the Smart City technology framework with local cultural values so that the development of smart cities becomes more inclusive, sustainable, and rooted in local wisdom. The research used a descriptive qualitative. The main data source in this research was obtained from informants. The initial informants were selected purposefully: people who understand problems in collaborative governance and smart cities. The research found that effective communication through face-to-face dialogue in development planning provides space for the community to convey aspirations, which become part of government policy. In addition, building trust between the government and the community has proven crucial in managing Smart City initiatives, especially in developing technological infrastructure such as CCTV surveillance systems and tourist alley revitalization programs. The commitment of local governments, the private sector, and active community participation in every stage of the implementation of the Sombere-based Smart City in Makassar reflects solid collaboration based on local cultural values. The limitations of this research emphasize the aspects of collaboration and cultural integration in Smart Cities but have not discussed in depth the technical and economic aspects that also affect the sustainability of Smart City.